Pelatihan Guru PAUD dalam Pengembangan Aktivitas Ekoliterasi Berbasis Budaya Sukoharjo - Pratiwi, Warih Anggi; Prehatiningsih, Arip; Maharani, Fitria; Sufiati, Vivi; Kusumastuti, Ika Aprilia; Faza, Miladia Wahda (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The increasing environmental degradation demands the integration of eco-literacy education from an early age. Early Childhood Education (ECE) plays a strategic role in instilling environmental conservation values through contextual and relevant learning experiences. This community service activity aims to enhance the understanding and skills of ECE teachers at BA Aisyiyah Rejosari, Sukoharjo Regency, in developing eco-literacy-based learning activities integrated with local culture. The implementation was carried out through two sessions of participatory educational training, which included material delivery, hands-on practice, workshops, and mentoring. The results showed that teachers gained a better understanding of eco-literacy concepts and were able to design learning activities such as making traditional herbal drinks, eco-print batik, and simple waste management practices with children. The children appeared enthusiastic and actively engaged in the learning process. Furthermore, the program fostered early environmental awareness and nurtured an appreciation for local cultural heritage. Therefore, this activity was deemed effective in enhancing teacher capacity and the quality of ECE learning, based on environmental values and local wisdom, in a sustainable manner